An integrated development strategy - Asplund, Gisele (Wiley New YorkUS, 1982)
Bridges the areas of business policy, marketing etc. on one side and behavioural organizational change and learning on the other. Argues that these two areas must be successfully integrated if thorough and lasting change is to occur and suggests that certain specific techniques must be used in order to handle an integrated change process.